Teacher’s communication competences as a part of pre-gradual preparation - MÁLKOVÁ, Jitka (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2010)
Communication is the basis of all our interpersonal relationships. This paper deals with oral communication as a means of realisation of pedagogic interaction. Improving communication skills to achieve required standard of communication competences is an especially important goal of pre-gradual preparation of future teachers. The initial part of the following text provides a short introduction to verbal and nonverbal means of pedagogic interaction realized during the learning process and emphasizes the importance of cultivated communication at school. The central section relates to pre-gradual preparation of future teachers, which includes cultivation of verbal means and purposeful usage of acoustic means. Also some principles of body language with their function are mentioned. This part provides a conceptual framework for communication courses at the college level. The final part is concerned with basic methodological principles which influence the successful pre-gradual preparation.
Keywords: Czech language; Glottodidactics; Communication competences; Oral language